The Relationship Between Infidelity Behavior and Normative Ethics in a Philosophical Perspective: Normative Ethics in a Philosophical Perspective” - baehaqqi, umar rasyiid; Akbar, Haiqal Radityan; karomah, affifatun nur; rosdiana, maulida (Maliki Interdisciplinary Journal, 2026)
Harmony in a household often gives rise to various problems, one of which is infidelity. Infidelity is a moral violation that has a strong influence and causes significant impacts within the institution of marriage. This study aims to analyze the phenomenon of infidelity by using the framework of normative ethics and moral philosophy, particularly in explaining how ethical values such as loyalty, honesty, and justice are established. The method used in this research is library research, focusing on examining theories of deontological ethics and utilitarianism to evaluate the moral goodness or badness of infidelity. The results of the analysis show that from the perspective of normative ethics, infidelity is consistently considered an act that violates moral duties (deontology) and produces significant harm (utilitarianism) to the betrayed party, thereby undermining the fundamental ethical values essential for maintaining harmony in interpersonal relationships.